Impact of maternal whole-cell or acellular pertussis primary immunization on neonatal immune response - Martin Aispuro, Pablo; Bottero, Daniela; Zurita, María Eugenia; Gaillard, María Emilia; Hozbor, Daniela Flavia (Frontiers in Immunology, 2023)
With the introduction of pertussis immunization for pregnant women in many countries, there has been renewed interest in the impact of whole-cell-pertussis vaccine (wP) versus acellular vaccine (aP) on disease control, particularly regarding the best approach for priming. To gather evidence on this topic, we analyzed the impact of aP or wP priming on aP vaccination during pregnancy (aPpreg) in mice. Two-mother vaccination schemes were employed (wP-wP-aPpreg and aP-aP-aPpreg), and the immune response in the mothers and their offspring, as well as the protection of the offspring against Bordetella pertussis challenge, were assessed. Pertussis toxin (PTx)-specific IgG responses were detected in mothers after both the second and third doses, with higher titers after the third dose, regardless of the vaccination schedule. However, a significant reduction in PTx-IgG-levels was observed after 22weeks post aPpreg immunization in mothers with the aP-aP-aPpreg scheme but not in the wP-wP-aPpreg immunized mothers. The aP-aP-aPpreg schedule triggered a murine antibody response mainly to a Th2-profile, while wP-wP-aPpreg induced a Th1/Th2 mixed profile. Both immunization schemes administered to the mothers protected the offspring against pertussis, but the wP-wP-aPpreg vaccination conferred offspring protection in all pregnancies at least up to 20weeks after receiving the aPpreg-dose. In contrast, the immunity induced by aP-aP-aPpreg began to decline in births that occurred 18 weeks after receiving the aPpreg dose. For the aP-aP-aPpreg scheme, pups born from gestations furthest from aPpreg (+22weeks) had lower PTx-specific-IgG levels than those born closer to the application of the dose during pregnancy. In contrast, for pups born to wP-wP-aPpreg vaccinated mothers, the PTx-specific-IgG levels were maintained over time, even for those born at the longest time studied (+22weeks). It is noteworthy that only the pups born from mothers with aP-aP-aPpreg and receiving a neonatal dose of either aP or wP were more susceptible to B. pertussis infection than mice with only maternal immunity, suggesting interference with the induced immunity (p<0.05). However, it should be noted that mice with maternal immunity, whether vaccinated or not with neonatal doses, are better protected against colonization with B. pertussis than mice without maternal immunity but vaccinated with aP or wP.